Advances in computational intelligence systems : contributions presented at the 18th UK Workshop on Computational Intelligence, September 5-7, 2018, Nottingham, UK /: contributions presented at the 18th UK Workshop on Computational Intelligence, September 5-7, 2018, Nottingham, UK. ([2019]) - Unknown
No abstract available